A sensitive and low background fluorescent sensing strategy based on g-C3N4–MnO2 sandwich nanocomposite and liposome amplification for ricin detection. Issue 23 (18th October 2018) - Men, Chen; Li, Chun Hong; Wei, Xue Mei; Liu, Jia Jun; Liu, Yu Xin; Huang, Cheng Zhi; Zhen, Shu Jun
Abstract : A novel liposome amplification strategy is developed for ricin B-chain (RTB) detection by using g-C3 N4 -MnO2 sandwich nanocomposite as a low background signal platform. Abstract : Ricin is an extremely potent ribosome-inactivating protein and serves as a likely food biocontaminant or biological weapon. Thus, simple, sensitive and accurate analytical assays capable of detecting ricin are urgently needed to be established. Herein, we present a novel method for ricin B-chain (RTB) detection by using two materials: (a) a highly efficient hybrid probe that was formed by linking a glucose oxidase (GOD)-encapsulated liposome (GOD-L) to magnetic beads (MBs) through hybridization between an aptamer and a blocker and (b) a new low-background g-C3 N4 –MnO2 sandwich nanocomposite that exhibits fluorescence resonance energy transfer (FRET) between the g-C3 N4 nanosheet and MnO2 . In the presence of RTB, the strong binding between RTB and the aptamer can release the blocker-linked liposome from the surface of the MBs. After magnetic separation, the decomposed liposome can release GOD to catalyze the oxidation of glucose, generating a certain amount of H2 O2 . Then, H2 O2 can reduce MnO2 of the g-C3 N4 –MnO2 nanocomposite to Mn 2+, which leads to the elimination of FRET. Thus, the fluorescence of the g-C3 N4 nanosheet will be turned on. Because of the excellent signal amplification ability of liposome and the characteristic highly sensitive response of the g-C3 N4 –MnO2 nanocomposite toward H2 O2, RTB could be detected sensitively based on the significantly enhanced fluorescent intensity. The linear range of detection was from 0.25 μg mL −1 to 50 μg mL −1 and the limit of detection (LOD) was 190 ng mL −1 . Moreover, the proposed assay was successfully applied in the detection of the entire ricin toxin content in a castor seed.